Differences between the European and Eurasian Good Pharmacovigilance Practices - A. V. Matveev; A. E. Krasheninnikov; E. A. Matveeva; B. K. Romanov (Безопасность и риск фармакотерапии, 2021)
Good pharmacovigilance practices (GVP) of the Eurasian Economic Union (EAEU) were prepared based on the GVP of the European Medicines Agency that have been in force in the European Union (EU) since 2012. The EAEU GVP have been in force in the Russian Federation and the other EAEU member states since 2016. It is important to identify potential diﬀerences between the current regulations in order to harmonise requirements for the pharmacovigilance systems in the EU and EAEU. The aim of the study was to analyse and compare GVP requirements in the EU and EAEU. The analysis helped to identify diﬀerences in the structure and contents of GVP sections, the deﬁnitions of terms (EU GVP deﬁnitions are more detailed and supported by examples, subsections, and references to other documents). Moreover, supplements and annexes to the EU GVP contain ﬁgures, templates, examples, algorithms, and tables, which are missing in the EAEU GVP. Expert analysis of these diﬀerences as applied to assessment of the pharmacovigilance systems’ eﬀectiveness, and practical activities of marketing authorisation holders, medicine developers, and regulatory authorities, demonstrated that the two GVPs are suﬃciently harmonised and have very few diﬀerences. However, the number of diﬀerences between the documents increases, as changes are made to the EU GVP. A more comprehensive harmonisation of the EAEU GVP with the current version of the EU GVP will make it possible to develop and use uniform pharmacovigilance documents in the EU and EAEU, and will facilitate the introduction of EAEU medicines into the global pharmaceutical market.